EFEKTIVITAS PENYALURAN KREDIT USAHA RAKYAT (KUR) DALAM MENINGKATKAN USAHA KECIL DAN MENENGAH PADA BANK RAKYAT INDONESIA UNIT MANONDA PALU - Arwan, Arwan (Katalogis, 2018)
KUR which is one of the government's efforts in encouraging banks to channel capital credit to UMKM and Giving Cooperatives. People's Business Credit (KUR) aims to accelerate the development of economic activities in the real sector in the context of poverty alleviation and expansion as well as the expansion of employment opportunities, especially for UMKM around the working area of BRI Manonda unit. This research is analyzed descriptively qualitative. The informants in this study are Head of Marketing, Head of Credit, 2 Marketing, and 3 People small and medium entrepreneurs. The number of informants in the study ie 7 people who were withdrawn with the technique of purposive sampling.Techniques of collecting and retrieving data consists of observation, interviews, and documentation. The theory used in looking at the effectiveness criteria of an organization is determined by the five elements put forward by Gibson. The results showed that the Distribution of People's Business Credit (KUR) in Improving Small and Medium Enterprises in Bank Rakyat Indonesia ManondaPalu Unit effective, it can be seen from five aspects namely; first, the results of production achieved. Second, efficiency, because it can improve business.Third, satisfaction, namely improving the welfare of entrepreneurs. Fourth, the adjustment, which UMKM can adjust to other business competition. And the fifth, continuity, namely UMKM can run and develop in accordance with the potential that exists.